FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU MAKAN SEHAT PADA REMAJA SMA DI KOTA SEMARANG - Riendy Aanisah Putri; Zahroh Shaluhiyah; Aditya Kusumawati (Jurnal Kesehatan Masyarakat (Undip), 2020)
Non-communicable diseases (NCD) cause 73% of deaths in Indonesia. NCDs trends continue to show an increase and have been found in young populations. Non-communicable diseases can be prevented by implementing healthy eating behaviors since teenagers in order to prepare themselves to become healthy, productive, and quality adults. The purpose of this study was to analyze the factors that influence healthy eating behavior in high school adolescents in the city of Semarang. This type of research is descriptive analytic with cross sectional study design. Subjects were 111 high school adolescents in 16 high schools in Semarang City. The sampling technique used probability sampling techniques with simple random sampling. Data collection was carried out through interviews using a questionnaire and using food recall. Data analysis in this study used univariate and bivariate analysis. The results showed that 37.8% of respondents had healthy eating behavior and 62.2% of respondents had unhealthy eating behavior. The results of the bivariate analysis showed that there was a relationship between healthy eating behavior and the respondent's knowledge (p-value ꞊ 0.000), the attitude of the respondent (p-value ꞊ 0,000), attitudes and eating behavior on friends (p-value ꞊ 0,002), attitudes and eating behavior on parents (p-value ꞊ 0,041). This study concludes the importance of consuming healthy and varied foods and maintaining the portion of food according to the needs in order to meet the adequacy of energy, protein, fat, carbohydrates, and fiber. Researcher suggest to school institutions to provide more variety of healthy menus in school canteens at affordable prices and advise parents to support children behaving healthy by providing healthy foods that vary every day.